2011
DOI: 10.1002/lapl.201110107
|View full text |Cite
|
Sign up to set email alerts
|

Double-wall carbon nanotube absorber for passively mode-locked Yb3+:Sc2SiO5 laser

Abstract: Double-walled carbon nanotube saturable absorber (DWCNT-SA) fabricated by vertical evaporation method was first used in passively mode-locked Yb 3+ :Sc 2 SiO 5 (Yb:SSO) laser to our knowledge. The laser operated at a repetition frequency of 89 MHz with the central wavelength of 1062.6 nm. A pulse duration of 15 ps was produced with an average power of 818 mW and a highest pulse energy of 9.2 nJ for a DWCNT-SA mode-locked laser. In addition, laser pulses as short as 1.6 ps were generated by inserting a pair of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Recently, a new member of the CNT family, multiwalled carbon nanotubes (MWCNTs) [10,11] have also attracted much attention due to the fact that they possess many advantages in nonlinear optics. The growth of the MWCNT material does not need complicated techniques or special growing conditions, so its production yield is high for each growth.…”
mentioning
confidence: 99%
“…Recently, a new member of the CNT family, multiwalled carbon nanotubes (MWCNTs) [10,11] have also attracted much attention due to the fact that they possess many advantages in nonlinear optics. The growth of the MWCNT material does not need complicated techniques or special growing conditions, so its production yield is high for each growth.…”
mentioning
confidence: 99%
“…Er:SSO has been developed into a laser gain medium. [15] Passive mode-locking and CW laser performances of Yb:SSO [16][17][18][19] and Ho:SSO [20] crystal were also reported. The spectral behavior of Nd:SSO crystal showed that Nd:SSO would be a promising gain medium in solid-state lasers.…”
Section: Introductionmentioning
confidence: 94%
“…Just because so many advantages, it has become a popular gain medium in the research of ultrashort pulsed lasers. For the past few years, people have developed continuous wave (CW) laser, mode‐locked laser and chirped pulse amplifier with Yb:SSO crystal 9–17 . However, there is no report of passively Q‐switched Yb:SSO crystal laser up until now, to our knowledge.…”
Section: Introductionmentioning
confidence: 99%